2006
DOI: 10.1007/s00705-006-0824-x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Contra-Viral Therapy (ICVT); a new approach to the treatment of DNA virus infections

Abstract: The sequestration of cellular K(+) has been shown elsewhere to elicit a broad spectrum of antiviral activity. The obligatory, coupled cotransports of Na(+), K(+) and Cl(-) (NKCC1) and of Na(+) and K(+) (NKATPase) effect net cellular K(+) influx. We examined the effects of specific inhibitors of these transports; a cardiac glycoside (Digoxin) and a loop diuretic (Furosemide) on virus replication in vitro. The replication of the DNA viruses, herpes simplex virus, varicella zoster virus, human cytomegalovirus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…The potential of cardiotonic steroids as antiviral agents was recognized by Hartley et al (19), who reported that replication of adenovirus and three herpesviruses (herpes simplex virus [HSV], varicella-zoster virus [VZV], and cytomegalovirus [CMV]) was inhibited by digoxin. The overall effect was attributed to an inhibition of viral DNA synthesis due to lowered levels of intracellular K ϩ , though genome replication was not assessed directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of cardiotonic steroids as antiviral agents was recognized by Hartley et al (19), who reported that replication of adenovirus and three herpesviruses (herpes simplex virus [HSV], varicella-zoster virus [VZV], and cytomegalovirus [CMV]) was inhibited by digoxin. The overall effect was attributed to an inhibition of viral DNA synthesis due to lowered levels of intracellular K ϩ , though genome replication was not assessed directly.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent phase 2 trial testing digoxin, alone and in combination with furosemide (19), for treatment of cutaneous warts due to human papillomavirus has been completed (https://clinicaltrials .gov/show/NCT02333643), but results have not been reported. The documented antiviral activity of cardiotonic steroids against HIV-1 (31), multiple DNA viruses (adenovirus, human papillomavirus [HPV], and herpesvirus [19,63]), and several unrelated RNA viruses (alphaviruses, reoviruses, and vesicular stomatitis virus) (64) suggests that they mediate their antiviral activity through a common host cell function, such as RNA processing, required for viral gene expression. Greater understanding of the mechanism(s) by which digoxin and digitoxin act to effect such a dramatic reduction in virus essential medium (MEM) supplemented with 10% fetal calf serum (FCS) plus penicillin (100 U/ml) and streptomycin (100 g/ml).…”
Section: Discussionmentioning
confidence: 99%
“…The compounds used in this study and their mechanisms of action, when known, are listed in Table 1. Artemisinins (monomers and dimers), cardiac glycosides, and U0126 were reported to inhibit CMV replication and were therefore selected for this study (24)(25)(26)(27)(28)(29). The multikinase inhibitor sunitinib has not previously been reported to inhibit CMV replication, but other kinase inhibitors have been shown to inhibit CMV in vitro (30).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac glycosides (CG) have been reported to inhibit herpes simplex virus 1 (HSV-1) and HCMV (7,13). These compounds are prescribed for congestive heart failure, a condition in which they bind to and inhibit the activity of the Na ϩ ,K ϩ -ATPase pump (31).…”
mentioning
confidence: 99%